2022
DOI: 10.1158/1078-0432.ccr-21-3577
|View full text |Cite
|
Sign up to set email alerts
|

Olaparib Efficacy in Patients with Metastatic Castration-resistant Prostate Cancer and BRCA1, BRCA2, or ATM Alterations Identified by Testing Circulating Tumor DNA

Abstract: Purpose: The phase III PROfound study (NCT02987543) evaluated olaparib versus abiraterone or enzalutamide (control) in metastatic castration-resistant prostate cancer (mCRPC) with tumor homologous recombination repair (HRR) gene alterations. We present exploratory analyses on the use of ctDNA testing as an additional method to identify mCRPC patients with HRR gene alterations who may be eligible for olaparib treatment. Patients and Methods: Plasma samples collected during screening in PROfound were retrospecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Second, a recent exploratory analysis of the PROfound study evaluated the efficacy of olaparib in patients with BRCA/ATM mutations investigated by liquid biopsy, showing that the clinical outcome endpoints were similar to those reached in the cohort in which mutations had been studied with somatic testing [3,56]. Therefore, this study highlights that the liquid biopsy technique could be a test with the same prognostic and predictive value as somatic testing.…”
Section: Discussionmentioning
confidence: 60%
“…Second, a recent exploratory analysis of the PROfound study evaluated the efficacy of olaparib in patients with BRCA/ATM mutations investigated by liquid biopsy, showing that the clinical outcome endpoints were similar to those reached in the cohort in which mutations had been studied with somatic testing [3,56]. Therefore, this study highlights that the liquid biopsy technique could be a test with the same prognostic and predictive value as somatic testing.…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies have validated the feasibility of ctDNA in detecting mutations of HRR genes in breast and prostate cancers [33][34][35], but relevant studies are scarce in ovarian cancer. Our study obtained high concordance between ctDNA and tumour samples to detect BRCA /HRR mutations.…”
Section: Discussionmentioning
confidence: 99%
“…ATM is crucial for DNA repair and cell cycle control, and mutations can lead to increased cancer risk. The PROfound study showed improved OS with Olaparib for mCRPC patients with BRCA1/2 or ATM mutations, leading to FDA approval for Olaparib in these cases in May 2020 ( 30 ). ATM status is also key in deciding on platinum-based chemotherapy or immunotherapy, as they depend on the cell’s ability to repair DNA.…”
Section: Discussionmentioning
confidence: 99%